Notes from the Editors. (Monthly Review: An Independent Socialist Magazine, 2024)
The article discusses the lack of education on climate change in U.S. public schools. Despite a national survey showing that a majority of middle and high school science teachers discuss climate change in their classrooms, many do not teach that it is caused by human activity. This is reflected in textbooks, with some downplaying the scientific consensus on climate change or presenting misleading information. The article argues that the failure to teach about climate change is a result of a capitalist society prioritizing short-term profits over the survival of civilization and humanity.